Islamic Environmental Ethics: A Cultural Framework for Sustainable Resource Management and Global Ecological Stewardship - Basri, Syahrul; Adnan, Yudi; Widiastuty, Lilis; Asrul Syamsul, Muhammad; Indar, Indar (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Environmental ethics provides a moral framework for addressing sustainability challenges, emphasizing the ethical responsibility of humanity toward ecological preservation. This study explores Islamic environmental ethics, focusing on principles such as khalifah (stewardship), amanah (trust), and adl (justice), and their applications in sustainable practices, education, and policymaking. Using a systematic literature review, 72 sources were analyzed to identify key themes, including the theoretical foundations of Islamic environmental ethics, practical applications in daily practices and resource management, and implications for policy development. Findings demonstrate the transformative potential of Islamic teachings in fostering environmental stewardship, with examples such as eco-pesantren initiatives and sustainable agriculture illustrating successful integration into community practices. The study also highlights the significance of incorporating Islamic principles into education to cultivate eco-conscious behaviors and align sustainability efforts with cultural and religious values. By providing a comprehensive framework for integrating Islamic environmental ethics into global sustainability strategies, this research offers a culturally resonant approach to addressing environmental challenges. Future studies are recommended to assess the real-world applications of these principles across diverse contexts and their impact on long-term ecological sustainability.